Rhynchospora chiquicerradensis and Rhynchospora nucistipitata, new species from the Brazilian Cerrado and the Bolivian Chiquitano region - Filho, Pedro Joel Silva Da Silva; Nicoletti, Sabrina; Thomas, William Wayt (Phytotaxa, 2026)
Two new species of Rhynchospora sect. Tenues are described from savanna ecosystems in central South America. One of them, Rhynchospora chiquicerradensis, occurs in seasonally wet grasslands with sandy soils and on seepage slopes of the Cerrado domain, on sandstone outcrops with shallow soils and humid hillside seeps in the Chiquitano ecoregion of eastern Bolivia. The other, Rhynchospora nucistipitata, is restricted to humid grasslands and stream margins in the Cerrado domain of Brazil. The recognition of these taxa as distinct species is supported by detailed morphological analyses and by previously published phylogenetic evidence generated in earlier studies. A distribution map, preliminary conservation status assessments and images of the type specimens are also provided.